2021
DOI: 10.1101/2021.01.25.21250489
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Impact of COVID-19-related disruptions to measles, meningococcal A, and yellow fever vaccination in 10 countries

Abstract: SummaryBackgroundChildhood immunisation services have been disrupted by the COVID-19 pandemic. WHO recommends considering outbreak risk using epidemiological criteria when deciding whether to conduct preventive vaccination campaigns during the pandemic.MethodsWe used 2-3 models per infection to estimate the health impact of 50% reduced routine vaccination coverage in 2020 and delay of campaign vaccination from 2020 to 2021 for measles vaccination in Bangladesh, Chad, Ethiopia, Kenya, Nigeria, and South Sudan, … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 36 publications
0
31
2
1
Order By: Relevance
“…Despite disruptions to vaccination, in the short term the transmission risk of vaccine-preventable diseases might have been temporarily mitigated by mask use, physical distancing, and other types of preventive behaviours practised during the pandemic. As evidenced by past epidemics and modelling exercises, 45 , 46 substantive gaps in vaccine coverage increase the risk of vaccine-preventable disease outbreaks once COVID-19 prevention measures subside and individuals resume pre-pandemic social contact patterns. A recent study suggests a potential 10% increase in mortality from vaccine-preventable diseases as a result of pandemic-related disruptions to routine immunisation and other planned vaccination campaigns, 45 while other work has associated declines in doses with increases in polio cases in endemic countries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite disruptions to vaccination, in the short term the transmission risk of vaccine-preventable diseases might have been temporarily mitigated by mask use, physical distancing, and other types of preventive behaviours practised during the pandemic. As evidenced by past epidemics and modelling exercises, 45 , 46 substantive gaps in vaccine coverage increase the risk of vaccine-preventable disease outbreaks once COVID-19 prevention measures subside and individuals resume pre-pandemic social contact patterns. A recent study suggests a potential 10% increase in mortality from vaccine-preventable diseases as a result of pandemic-related disruptions to routine immunisation and other planned vaccination campaigns, 45 while other work has associated declines in doses with increases in polio cases in endemic countries.…”
Section: Discussionmentioning
confidence: 99%
“…As evidenced by past epidemics and modelling exercises, 45 , 46 substantive gaps in vaccine coverage increase the risk of vaccine-preventable disease outbreaks once COVID-19 prevention measures subside and individuals resume pre-pandemic social contact patterns. A recent study suggests a potential 10% increase in mortality from vaccine-preventable diseases as a result of pandemic-related disruptions to routine immunisation and other planned vaccination campaigns, 45 while other work has associated declines in doses with increases in polio cases in endemic countries. 6 Previous infectious disease outbreaks, such as the 2014 Ebola virus epidemic in west Africa, also led to large disruptions to routine immunisation and subsequent measles outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…mask wearing, hotel quarantine, lockdown strategies) [ 1 , 2 ]. While responses to the COVID-19 pandemic have reduced the spread of IMD and other communicable diseases [ 4 , 38 ], they have also impacted vaccination programs [ 3 , 39 ] and may negatively impact outbreak management strategies. The current delay between increased understanding of disease transmission and actual implementation into public health guidance can have direct and immediate consequences for individual and population health.…”
Section: Discussionmentioning
confidence: 99%
“…10 For vaccine campaigns, the risk of outbreaks as a result of postponing campaigns varies across settings and pathogens. 11 For some vaccines (e.g. meningococcal A), campaigns can be postponed in the short-term in many settings due to the persistence of immunity from past campaigns.…”
Section: Discussionmentioning
confidence: 99%
“…Previous modelling studies have demonstrated that the benefits of continuing routine immunisation likely outweigh the excess risk from COVID-19 but did not examine campaign delivery 10 . A recent study has examined risks of vaccine-preventable disease outbreaks (measles, meningococcal A, and Yellow Fever) associated with delaying immunisation campaigns, which varied across countries 11 . Another study assessed the risk of measles outbreaks in Kenya and found that although COVID-19 interventions also temporarily reduced the risk of an outbreak from measles immunity gaps, this risk rises rapidly once these restrictions are lifted highlighting the need to implement catch-up campaigns 12 .…”
Section: Introductionmentioning
confidence: 99%